Enhancing floral diversity: A review of mutation breeding techniques in flower crops - Vishwanath S; Rajangam J; Rajadurai K R; Gnanasekaran M; Anitha T; Ravi R (Plant Science Today, 2024)
Flower crops encompass a wide range of ornamental annuals and perennials that are commercially cultivated for aesthetic appeal of their floral displays. Mutation induction has been used since the early 20th century to increase genetic diversity and develop new flower varieties with improved yield, quality, adaptation and market value. Mutation experiments have successfully created genetic variability and novel phenotypes in diverse floral species. Mutation breeding, which involves the induction of genetic variations via physical and chemical mutagens, has emerged as a vital technique for enhancing ornamental plant traits, such as flower color, shape, disease resistance and stress tolerance. It explores the types and applications of physical mutagens, such as gamma rays and ion beams and chemical mutagens, such as ethyl methane sulfonate (EMS) and sodium azide (SA). This review provides detailed insights into mutation breeding research conducted on major flower crops (e.g., rose, carnation, chrysanthemum and gerbera). This study also highlights achievements in the development of novel flower varieties, highlights the key challenges faced in mutation breeding programs and identifies gaps in research, particularly concerning the comparative efficacy of different mutagens, environmental impacts and genetic stability of mutated varieties. Furthermore, the impact of mutation breeding on the global flower market is discussed, emphasizing its role in expanding trait diversity, catering to niche markets and enhancing the commercial value of flower crops. Mutation breeding offers significant promise in the development of sustainable and climate-resilient ornamental crops that can meet the needs of emerging markets. This review serves as a valuable resource for students, scientists and breeders interested in leveraging mutation breeding for floral crop improvement.